New Children of Israel: Emerging Jewish Communities in an Era of Globalization - Devir, Natan (University of Utah Press, 2017)
Contents -- List of Illustrations -- Acknowledgments -- Preface -- 1. Introduction -- 2. Structuralizing Nostalgia in Akanland: The âHouse of Israelâ of Ghana -- 3. Online Spiritual Volition: The âInternet Jewsâ of Cameroon -- 4. Political Revivalism as Religious Practice: The âChildren of Ephraimâ of India -- 5. Conclusion -- Notes -- Bibliography